2012
DOI: 10.1080/02699931.2012.665029
|View full text |Cite
|
Sign up to set email alerts
|

The social signal value of emotions

Abstract: Human interactions are replete with emotional exchanges. In these exchanges information about the emotional state of the interaction partners is only one type of information conveyed. In addition, emotion displays provide information about the interaction partners' disposition and the situation as such. That is, emotions serve as social signals. Acknowledging this role of emotions, this special section brings together research that illustrates how both person perception and situational understanding can be der… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
85
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(93 citation statements)
references
References 26 publications
6
85
0
2
Order By: Relevance
“…Whereas social approval and disapproval of someone's behaviour can be signalled in various ways, it has been suggested that emotions can serve this purpose quite effectively. That is, one important function of emotions is to foster the learning of social norms and their adoption (Elster, 1996;Hareli & Hess, 2012;Keltner & Haidt, 1999). In line with this claim, Schultz et al (2007) showed that people tended to align their gas consumption more to the norm when feedback about their monthly consumption relative to the norm was signalled by emoticons showing happy or sad faces than when such feedback was missing.…”
supporting
confidence: 50%
See 1 more Smart Citation
“…Whereas social approval and disapproval of someone's behaviour can be signalled in various ways, it has been suggested that emotions can serve this purpose quite effectively. That is, one important function of emotions is to foster the learning of social norms and their adoption (Elster, 1996;Hareli & Hess, 2012;Keltner & Haidt, 1999). In line with this claim, Schultz et al (2007) showed that people tended to align their gas consumption more to the norm when feedback about their monthly consumption relative to the norm was signalled by emoticons showing happy or sad faces than when such feedback was missing.…”
supporting
confidence: 50%
“…Emotion displays can be conceived of as containers of social information about the expresser and/or the situation in which the emotion was displayed (Hareli & Hess, 2012;Van Kleef, 2010;Weiner, 2006). Indeed, according to appraisal theories of emotion, emotions are elicited and differentiated through a series of appraisals of (internal or external) stimulus events based on the perceived nature of the event (Ellsworth & Scherer, 2003;Frijda, 1986).…”
mentioning
confidence: 99%
“…Notably, while the majority of research investigating categorical processing by social psychologists has been related to relatively stable characteristics such as race/ethnicity, gender, socio-economic status and EMOTIONS CAN CUE SOCIAL CATEGORIZATION COGNITION AND EMOTION, 2015 age, emotions may to some extent be assumed to be more context-dependent and variable. Even though these visible cues may be perceived to be less predictive of underlying personality traits, because of their importance in person perception (Hareli & Hess, 2012), they have the potential to spontaneously prompt categorical processing. In the present research we investigated whether facial expression related to anger, happiness and true and false smiles serve as cues of attentional control and result in categorical responding to even inconsistent members.…”
Section: The Present Researchmentioning
confidence: 99%
“…Facial expressions communicate information about the individual and the environment that elicits rapid responses in the observer (Niedenthal & Brauer, 2012). Such responses include inferences about the state of mind of the individual who expresses the emotion and changes in the observer's own behaviour to deal with the situation (Adams, Ambady, Macrae, & Kleck, 2006;Anderson & Thompson, 2004;Hareli & Hess, 2012;Keltner & Kring, 1998;Marsh, Kozak, & Ambady, 2007) Although social psychologists have explored the types of information conveyed by facial expressions, less is known about whether and how facial expressions serve to regulate cognitive processing in observers. The present set of experiments was designed to explore whether facial expressions of emotion can cue attentional control similarly to classic social categories such as gender (Fiske & Neuberg, 1990).…”
mentioning
confidence: 99%
“…This derives from the behavioural ecology view of emotion expressions as signals of intent toward other individuals (Hinde, 1985;Fridlund, 1994), as well as perspectives on the communicative and inter-personal functions of emotions (Fischer & Manstead, 2008;Giner-Sorolla, 2012;Hareli & Hess, 2012;Parkinson, 2005;Van Kleef, 2009). …”
mentioning
confidence: 99%